2021
DOI: 10.3390/agronomy12010058
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality Prediction of Winter Rapeseed—Artificial Neural Network and Random Forest Models

Abstract: As one of the greatest agricultural challenges, yield prediction is an important issue for producers, stakeholders, and the global trade market. Most of the variation in yield is attributed to environmental factors such as climate conditions, soil type and cultivation practices. Artificial neural networks (ANNs) and random forest regression (RFR) are machine learning tools that are used unambiguously for crop yield prediction. There is limited research regarding the application of these mathematical models for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…On the contrary, the model for the antioxidant activity seemed to predict data accurately (RMSE < 0.2) as well as those for the titratable acidity and the total soluble solids seemed to work well (Table 4). A recent study suggested that ANN modeling can be successfully exploited for the evaluation of the same qualitative parameters [61]. To estimate the relative importance of the input variables to ANN model predictions, sensitivity analysis was carried out.…”
Section: Prediction Of Strawberries Quality Attributesmentioning
confidence: 99%
“…On the contrary, the model for the antioxidant activity seemed to predict data accurately (RMSE < 0.2) as well as those for the titratable acidity and the total soluble solids seemed to work well (Table 4). A recent study suggested that ANN modeling can be successfully exploited for the evaluation of the same qualitative parameters [61]. To estimate the relative importance of the input variables to ANN model predictions, sensitivity analysis was carried out.…”
Section: Prediction Of Strawberries Quality Attributesmentioning
confidence: 99%
“…In the studies by Amoriello et al [ 28 ] and Yoshioka et al [ 82 ], they discovered that ANN models could accurately predict anthocyanins by taking into account the CIELab coordinates of L*, a*, and b*. A recent study suggested that ANN modeling can be successfully exploited for the prediction of quality parameters of winter rapeseed [ 83 ]. Furthermore, ANN was developed to predict the TSS, titratable acidity, TSS/titratable acidity, anthocyanin, vitamin C, and total carotenoids contents using surface-color CIELab coordinates of L*, hue, and chroma for fresh peach fruit based on inputs of juice volume, single fruit weight, and sphericity percent [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…The computational confirmation of the constructed non-linear model was tested using standard statistical tests, such as relative absolute error (RAE), root mean square error (RMSE), and relative standard error (RSE). These commonly used parameters can be calculated as follows [42,43]:…”
Section: Performance Indicatorsmentioning
confidence: 99%